1998
DOI: 10.1097/00002030-199801000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of HIV infection among women using family planning methods in Dar es Salaam, Tanzania

Abstract: These findings confirm that a large number of new HIV infections continue to occur in this population. Reassuringly, no significant association was observed between HIV and use of specific contraceptive methods. Interventions to reduce further spread of HIV are still urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 29 publications
2
115
0
2
Order By: Relevance
“…The first study describes a protective effect but had considerable loss-to-follow-up and possible misclassification of the partners' circumcision status. 63 The other study showed nonsignificant protection in the high-risk group (ie, women who were more likely to have ever engaged in sex work; to have reported 2 or more partners in the last 3 months; and/or to have had a higher median lifetime number of sex partners) but neither protection nor increased risk in the study population as a whole. 64 A metaanalysis with good evidence of data from 1 randomized controlled trial (RCT) and 6 longitudinal analyses found little evidence that male circumcision directly reduces their female partner' s risk of acquiring HIV (summary relative risk: 0.8 [95% confidence interval (CI): 0.53-1.36]); however, male circumcision' s protective effect did not reach a level of statistical significance.…”
Section: Heterosexual Womenmentioning
confidence: 84%
“…The first study describes a protective effect but had considerable loss-to-follow-up and possible misclassification of the partners' circumcision status. 63 The other study showed nonsignificant protection in the high-risk group (ie, women who were more likely to have ever engaged in sex work; to have reported 2 or more partners in the last 3 months; and/or to have had a higher median lifetime number of sex partners) but neither protection nor increased risk in the study population as a whole. 64 A metaanalysis with good evidence of data from 1 randomized controlled trial (RCT) and 6 longitudinal analyses found little evidence that male circumcision directly reduces their female partner' s risk of acquiring HIV (summary relative risk: 0.8 [95% confidence interval (CI): 0.53-1.36]); however, male circumcision' s protective effect did not reach a level of statistical significance.…”
Section: Heterosexual Womenmentioning
confidence: 84%
“…Of the 20 studies included in Fisher and colleagues' meta-analysis, 19 were retained for inclusion in the present study (Ao, Sam, Masenga, Seage, & Kapiga, 2006;Ayisi et al, 2000;Braddick et al, 1990;Demissie, Amre, & Tsega, 1996;Fritz et al, 2002;Hargreaves et al, 2002;Kapiga, Lyamuya, Lwihula, & Hunter, 1998;Kapiga et al, 2002;Kapiga et al, 2006;Lewis et al, 2005;Mbulaiteye et al, 2000;Mnyika, Klepp, Kvåle, & Ole-King'ori, 1996;Ndina-Achola et al, 1997;Sebit et al, 2003;Simbayi et al, 2004;Talbot et al, 2002;Tengia-Kessey, Msamanga, & Moshino, 1998;Zablotska et al, 2006;Zuma, Gouws, Williams, & Lurie, 2003) and one (Gilgen, Williams, & Campbell, 2000) was excluded for failing to meet the inclusion criteria specified below (i.e., it was not published in a peer-reviewed journal). An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St.…”
Section: Methods Literature Reviewmentioning
confidence: 99%
“…a period of 1 to 3 years). Even though condom use was comparable between alcohol drinkers and non-drinkers, sero-conversion risk was found to be higher for those who consumed alcohol (Kapiga et al, 1998). In a Tanzanian sample of men, Ghebremichael and Paintsil (2009) found condom use with a main partner to be low after alcohol consumption in a sample of 789 men, even though 6.5% of the subjects were identified to be HIV-positive.…”
Section: Heterosexual Couples Outside Of the United Statesmentioning
confidence: 86%
“…In a sample of 1370 women in Tanzania, Kapiga et al (1998) observed that 5.5% of their s a m p l e ( 3 . 8 % o f n o n -d r i n k e r s a n d 9 .…”
Section: Heterosexual Couples Outside Of the United Statesmentioning
confidence: 99%